Association of skin temperature, cumulative dose of radiation, and the diagnosis of radiodermatitis - Dryelle Soster Iede Shiguihara; Leandra Ulbricht; Eduardo Borba Neves (Bioscience Journal)
Radiotherapy is one of the treatments of cancer, and radiodermatitis is one of the side effects, with a negative impact on the patient's quality of life, which can lead to limitation dose of radiation, delay in completion, or discontinuation of treatment. Recent studies show evidence that thermography can be useful in this context of radiodermatitis, as it is a technology that has been improved, there are still few studies showing thermal response and mapping of radiation dermatitis. This study analyzed the association between skin temperature, cumulative radiation dose, and the appearance of radiodermatitis. The research was carried out with 76 participants with skin, head or neck cancer and thermographic recording immediately before and after irradiation. The Radiation Therapy Oncology Group scale was used to diagnose radiodermatitis. As the main results in our sample, 70% of the participants had some degree of radiodermatitis, and significant differences in skin temperature were observed when compared to participants without (32.88 °C) and with radiodermatitis (thermal difference in average temperature greater than 1.0 °C for both grade I and grade II radiodermatitis). The ideal time for thermographic evaluation would be after receiving the daily dose, where we found a moderate correlation (0.474) between the temperature of the affected side after irradiation and the pre-irradiation cumulative dose. Our results demonstrate that radiodermatitis change skin temperature and thermographic analysis can quantify. Finally, to improve early diagnosis, we recommend that scales be constructed with greater definitions for the classification of radiation toxicity, without overlapping symptoms, considering quantitative criteria.